Predicting Financial Distress based on Corporate Actions - Mohamad, Azhar (2016)
In spite of abundant literature on financial distress prediction modeling, corpus of empirical work on predictive capacity of corporate actions is scant. The prevalent norm of using accounting information suffers from being out-dated quickly, whereas corporate actions of firms are typically disclosed promptly. This study investigates which corporate actions can help to predict financial distress and to examine whether prediction of financial distress using corporate actions can improve classification accuracy vis-à-vis accounting ratios. Additional comparison is carried out based on a combination of accounting ratios and corporate actions as well as models wherein information is incorporated separately. We find that the frequency of new issue of capital and frequency of changes in Audit Committee are significant predictors of financial distress. Furthermore, we also find that Working Capital to Total Assets Ratio and Asset Turnover Ratio are reliable predictors of financial distress among the accounting ratios.